2003
DOI: 10.1161/01.cir.0000051361.69808.3a
|View full text |Cite
|
Sign up to set email alerts
|

Selective COX-2 Inhibition Improves Endothelial Function in Coronary Artery Disease

Abstract: Background— There is an ongoing debate as to whether the gastrointestinal safety of COX-2 inhibition compared with nonsteroidal antiinflammatory drugs (NSAIDs) may come at the cost of increased cardiovascular events. In view of the large number of patients at cardiovascular risk requiring chronic analgesic therapy with COX-2 inhibitors for arthritic and other inflammatory conditions, the effects of selective COX-2 inhibition on clinically useful surrogates for cardiovascular disease, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
207
2
12

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(230 citation statements)
references
References 55 publications
9
207
2
12
Order By: Relevance
“…26 Interestingly, reducing CRP levels over time is associated with improvement of endothelium-dependent vasodilation in patients with coronary artery disease. 25,27 In this study, xuezhikang had a potent effect on lowering CRP, which was associated with improvement of fasting FMD. This supports the hypothesis that xuezhikang may protect endothelial function partly through an antiinflammatory mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…26 Interestingly, reducing CRP levels over time is associated with improvement of endothelium-dependent vasodilation in patients with coronary artery disease. 25,27 In this study, xuezhikang had a potent effect on lowering CRP, which was associated with improvement of fasting FMD. This supports the hypothesis that xuezhikang may protect endothelial function partly through an antiinflammatory mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…Investigation of possible mechanisms, by which low-dose aspirin can influence on BP of patients with AH and hypercholesterolaemia Improvement of endothelial function was shown in acute studies, 28,29 while results of chronic trials are conflicting [30][31][32] Our study demonstrates that addition of low-dose aspirin in hypertensive and hypercholesterolaemic subjects on top of antihypertensive and statins improves endothelial function and reduces BP Homogeneity of the studied population. Demonstration of synergistic interactions between aspirin and statins on BP reduction via improvement of NOmediated endothelial function Small study.…”
Section: Low-dose Aspirin On Bp In Hypertensive Patientsmentioning
confidence: 73%
“…29 Results of chronic trials are conflicting. [30][31][32] Since other COX inhibitors showed no beneficial vascular effects, aspirin might exhibit a vasculoprotective, COX-independent mechanism. Recently, Taubert et al 33 demonstrated that therapeutically relevant concentrations of aspirin elicit nitric oxide (NO) release from vascular endothelium due to a direct acetylation of the eNOS protein, but is independent of COX inhibition or inhibition of superoxidemediated NO degradation.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report showing that rofecoxib possesses antioxidative property and inhibits Ang II-induced cardiovascular alterations. Recent data indicated that selective COX-2 inhibition by celecoxib reduces oxidized LDL in patients with coronary artery disease, 15 slightly decreased salt-induced hypertension, and normalized the indicator of oxidative stress, 8-isoprostane, in hypertensive rats. 16 However, different from our result, rofecoxib (2 mg/kg per day) treatment did not show any antioxidative effect in those salt-induced hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%